The Brain Symptom and Impact Questionnaire in brain metastases patients: a prospective long-term follow-up study. (January 2016) - Pulenzas, Natalie; Ray, Saurabh; Zhang, Liying; McDonald, Rachel; Cella, David; Rowbottom, Leigha; Sahgal, Arjun; Soliman, Hany; Tsao, May; Danjoux, Cyril; Lechner, Breanne; Chow, Edward
Aims: To assess the ability of the Brain Metastases Symptom and Impact Questionnaire (BASIQ) in evaluating symptoms and impact on daily life.Patients & methods: Patients with brain metastases completed BASIQ, Functional Assessment of Cancer Therapy-General, FACT-Brain at baseline and at 1, 2 and 3 months follow-ups.Results: Thirty-six patients completed all follow-ups. BASIQ correlated well (r ≥ 0.40) with FACT subscales, except for social/family and emotional wellbeing. Linear regression analysis found no significant changes in quality of life (QOL) over time in both the BASIQ and FACT scales. Therefore, the two questionnaires coincide as both detected nonchanges.Conclusion: The ability of the BASIQ in evaluating symptoms and impact on over longer assessment periods was supported by the FACT questionnaires.